La violencia intrafamiliar en la ciudad de Ibarra: análisis comparativo de los contextos pre pandemia y durante la pandemia (años 2019 y 2020) - Flores Yépez, Josselyn Solange (2024)
Society evolves in line with the needs of individuals, with the intention that everyone exercises their rights and obligations, throughout social development, a repetitive behavior has been evident in every environment. Thus, domestic violence has become a constant phenomenon within households. The significance of exploring this topic in a study lies in raising awareness within society to stop normalizing domestic violence in the everyday lives of families. The overall objective was to determine the impact of COVID-19 on domestic violence in Ibarra during the period 2019-2020. A mixed approach based on documentary material and an analytical-inductive and socio-legal method was employed through document review and other research techniques to highlight the issue of violence against women during the pandemic in Ibarra. Through a documentary analysis based on generalities, national and international regulations, and information gathered from interviews with public servants specialized in gender-based violence and domestic violence, it was found that in the year 2020, during the health emergency, the rate of domestic violence reports substantially increased compared to 2019, according to data provided by the Attorney General's Office in the City of Ibarra. The conclusion within this research focuses on the fact that, although Ecuadorian regulations incorporate the use of international standards such as the Belém do Pará and The Convention on the Elimination of All Forms of Discrimination against Women conventions within the domestic violence process, limitations and challenges persist both within and outside the health emergency. On the other hand, data on the domestic violence index also show some increase during the year 2020.